Hexaamino triphenyl-based two-dimensional covalent organic framework material as well as preparation method and application thereof
Through solvothermal method and ultrasonic techniques, two-dimensional covalent organic frame materials with different pore sizes and high stability were prepared, which solved the problems of high production cycle and cost and difficulty in topological control in the existing technology, and achieved efficient Hydrolytic catalysis, photocatalysis and drug delivery applications.
Patent Information
- Application Number
- CN202310833322.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-07
- Publication Date
- 2025-01-07
AI Technical Summary
The prior art requires the use of specially designed monomers and changing experimental conditions when preparing stable two-dimensional covalent organic frame materials, which increases production cycle and cost, and it is difficult to accurately manipulate the topology to regulate its optoelectronic properties.
By using the same group of monomers and solvent thermal methods, combined with ultrasonic, vacuum-freeze-nitrification-transfer nitrogen circulation and other steps, two-dimensional covalent organic frame materials with different pore sizes, high crystallinity and good chemical stability were prepared, including HT -COFs and BI-HT-COFs, and improve their application performance through metal composite Pd/HT-COFs.
It has achieved selective synthesis of covalent organic framework materials with different pore sizes from the same precursor, with high crystallinity, good chemical and thermal stability, and is suitable for the fields of electrolytic water catalysis, photocatalysis, drug delivery and gas separation.
Smart Images

Figure CN119264354A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of two-dimensional covalent organic framework materials, and specifically relates to a two-dimensional covalent organic framework material based on hexamidotriphenyl group and a preparation method and application of the topological structure regulation thereof. Background Art
[0002] Two-dimensional (2D) covalent organic frameworks (COFs) constructed from small molecules with high symmetry have attracted great attention in recent years. They are laterally infinite, one-atom and porous frameworks with long-range order in the 2D plane.
[0003] Establishing effective charge transport pathways, such as pathways through bonds and pathways through space, plays a key role in the preparation of conductive 2DCOFs (X. Feng, X. Ding, D. Jiang. Chem. Soc. Rev. 2012, 41, 6010). Compared with graphene, the two-dimensional porous structure of sp2-hybridized carbon with adjustable band structure is expected to provide greater flexibility in composition, structure and physical properties. Compared with amorphous organic polymers, COFs can grow discrete organic molecular building blocks into a clear polygonal extended structure with permanent pores and controllable pore size by topologically guiding discrete organic molecules through strong covalent bonds (LA Baldwin, JW Crowe, DAPyles, PLJAm. Chem. Soc. 2016, 138, 15134). The polymorphism of the topological structure of COFs has a very important influence on its photoelectronic and photocatalytic properties. Constructing 2D conjugated COFs with controlled topology and unique functions is a long-sought goal due to their great potential in separation (H. Wang, C. Qian, J. Liu, Y. Zeng, D. Wang, W. Zhou, L. Gu, H. Wu, G. Liu, Y. Zhao, J. Am. Chem. Soc. 2020, 142, 4862; Y. Wang, M. Xie, J. Lan, L. Yuan, J. Yu, J. Li, J. Peng, Z. Chai, J. K. Gibson, M. Zhai, W. Shi, ...). 2020, 6, 2796), energy storage (S. Gu, S. Wu, L. Cao, M. Li, N. Qin, J. Zhu, Z. Wang, Y. Li, Z. Li, J. Chen, Z. Lu, J. Am. Chem. Soc. 2019, 141, 9623), catalysis (M. Li, S. Qiao, Y. Zheng, YH Andaloussi, X. Li, Z. Zhang, A. Li, P. Cheng, S. Ma, Y. Chen, J. Am. Chem. Soc. 2020, 142, 6675) and nanoelectronics (K. Geng, T. He, R. Liu, S. Dalapati, KT Tan, Z. Li, S. Tao, Y. Gong, Q. Jiang, D. Jiang, Chem Rev 2020, 120, 8814).
[0004] Various 2DCOFs with different topological structures have been designed by utilizing different bonding relationships and symmetric topological structures between monomers. The Schiff base condensation reaction is a reaction that forms an imine bond between amine and aldehyde precursors under reversible conditions, and has been widely explored in the synthesis of highly crystalline 2DCOFs. It is worth noting that the polymorphism of the topological structure of COFs has a very important influence on its optoelectronic properties and applications (Y. Meng, Y. Luo, JL Shi, H. Ding, X. Lang, W. Chen, A. Zheng, J. Sun, C. Wang, Angew Chem Int Ed Engl 2020, 59, 3624). By fixing the reversible imine connection through the aza-DielsAlder cyclization reaction kinetics, the imine-linked COFs can be transformed into ultra-stable porous aromatic frameworks. In particular, nitrogen-doped π-conjugated microporous COFs show excellent chemical stability and extended p-delocalization, which is very useful for high on-off rate optical switches and photovoltaic cells (L. Cusin, H. Peng, A. Ciesielski, P. Samori, Angew Chem Int Ed Engl 2021, 60, 14236). Based on framework reconstruction, the pore size of 2DCOFs can be adjusted, and the crystallinity of the reconstructed COFs is greatly enhanced, the porosity is greatly improved, and the charge carrier transport is also improved.
[0005] Most of the conversion strategies for stable 2D COFs currently used are based on reversible Schiff base reactions followed by closed polymerization, which not only requires the use of specially designed monomers, changes in experimental conditions and processes, but also increases production cycles and costs. Currently, it is a challenging goal to produce the desired topological structure in a selective manner. Therefore, the exploration of precisely manipulating the topological structure of 2D COFs to regulate their optoelectronic properties and thus improve their application performance is a research hotspot in this field. Summary of the invention
[0006] The purpose of the present invention is to provide a two-dimensional covalent organic framework material based on hexaaminotriphenyl group and a preparation method and application of its topological structure regulation. By using the same group of monomers and a solvothermal method, two two-dimensional covalent organic frameworks with different pore sizes, high crystallinity, good chemical stability and thermal stability are prepared, which can be used in the fields of water electrolysis catalysis, photocatalysis, drug delivery, gas separation and the like.
[0007] To achieve the above object, the present invention provides the following technical solutions:
[0008] In a first aspect, the present invention provides a method for preparing a two-dimensional covalent organic framework material, comprising the following steps:
[0009] S1, dissolving a monomer A containing an amino functional group and a monomer B containing an aldehyde functional group in a mixed solvent, adding a catalyst of acetic acid or p-toluenesulfonic acid, and ultrasonicating to obtain a mixed solution;
[0010] S2. After the mixed solution is subjected to a vacuum-freezing-nitrogen circulation cycle, the tube is sealed for polymerization, and the system is allowed to stand until the system returns to room temperature, and then post-processed to obtain a two-dimensional covalent organic framework material HT-COFs or BI-HT-COFs.
[0011] In step S1, the monomer A is 2,3,6,7,10,11-hexamidotriphenylhexahydrochloride (HATP).
[0012] In step S1, the monomer B is 1,4-phthalaldehyde (TPA) and / or 2,5-dimethoxybenzene-1,4-dicarboxaldehyde (DTPA).
[0013] In step S1, the molar ratio of the monomer A to the monomer B is (0.3-1):1; preferably 0.3:1 and 0.6:1.
[0014] In step S1, the mixed solvent is composed of dioxane and mesitylene in a molar ratio of (0.1-1):1, preferably 1:1.
[0015] In step S1, the catalyst is added in the form of an aqueous solution.
[0016] In step S1, the concentration of the aqueous solution of acetic acid is 1-6M, preferably 1M.
[0017] In step S1, the concentration of the aqueous solution of p-toluenesulfonic acid is 1-6M, preferably 1.4M.
[0018] In step S1, the ultrasonic conditions are: time is 10-100 min, preferably 20 min; ultrasonic frequency is 1-100 Hz, preferably 80 Hz.
[0019] In step S1, the catalyst is acetic acid, and in the corresponding mixed solution, the concentration of the monomer A is 10-20 mg / mL, preferably 15 mg / mL; the concentration of the monomer B is 6-12 mg / mL, preferably 12 mg / mL.
[0020] In step S1, the catalyst is p-toluenesulfonic acid, and in the corresponding mixed solution, the concentration of the monomer A is 10-20 mg / mL, preferably 15 mg / mL; the concentration of the monomer B is 6-12 mg / mL, preferably 6 mg / mL.
[0021] In step S2, the conditions of the vacuum-freezing-nitrogen circulation are: temperature of 75-80K, preferably 77K, number of times of 1-6 times, preferably 2 times.
[0022] In step S2, the standing conditions are: temperature of 60-150°C, preferably 150°C, and time of 3 days to 15 days, preferably 14 days.
[0023] In step S2, the post-treatment includes: suction filtration, solvent washing, and vacuum drying.
[0024] The solvent used in the solvent washing is at least one of methanol, dichloromethane, tetrahydrofuran and ethanol, preferably dichloromethane and tetrahydrofuran.
[0025] The vacuum drying conditions are as follows: temperature of 90-120° C., preferably 100° C.; vacuum degree of 133-267 Pa, preferably 133 Pa.
[0026] In a second aspect, the present invention further provides a two-dimensional covalent organic framework material obtained by the preparation method; the two-dimensional covalent organic framework material is an imine-linked two-dimensional covalent organic framework HT-COFs or an imidazole-linked two-dimensional covalent organic framework BI-HT-COFs.
[0027] The structural formula of the HT-COFs is as follows:
[0028]
[0029] The obtained HT-COFs have a double pore structure. The double pore structure refers to a triangular pore structure with two sizes in the structure. Specifically, the obtained HT-COFs have two pore sizes of ~1nm and ~1.3nm, and the specific surface area is 200-466m 2 / g, preferably 466m 2 / g.
[0030] The structural formula of the BI-HT-COFs is as follows:
[0031]
[0032] The BI-HT-COFs have a single-pore structure. A single-pore structure refers to a hexagonal pore structure in the structure. Specifically, the BI-HT-COFs have a uniform pore size of 2.5 nm and a specific surface area of 200-532 m 2 / g, preferably 532m 2 / g.
[0033] In a third aspect, the present invention further provides a two-dimensional covalent organic framework metal composite material, comprising the following components: a carrier HT-COFs and Pd loaded on the HT-COFs.
[0034] In a fourth aspect, the present invention further provides a method for preparing the two-dimensional covalent organic framework metal composite material, comprising the following steps: adding the HT-COFs and a palladium source into a solvent, stirring, and post-treating to obtain the two-dimensional covalent organic framework metal composite material Pd / HT-COFs.
[0035] The palladium source is one or more of palladium acetate, palladium chloride and palladium pivalate, preferably palladium acetate.
[0036] The solvent is one or more of dichloromethane, chloroform and acetonitrile, preferably dichloromethane.
[0037] In the stirred system, the concentration of the HT-COFs is 0.1-5 mg / mL, preferably 0.5 mg / mL; the concentration of the palladium source is 0.5-25 mg / mL, preferably 1 mg / mL.
[0038] The stirring conditions are: temperature of 15-35°C, preferably 25°C, and time of 1 day to 3 days, preferably 1 day.
[0039] The post-treatment includes: suction filtration, solvent washing and vacuum drying.
[0040] The solvent used in the solvent washing is at least one of methanol, dichloromethane, tetrahydrofuran and ethanol, preferably dichloromethane and tetrahydrofuran.
[0041] The vacuum drying conditions are as follows: temperature of 90-120° C., preferably 100° C.; vacuum degree of 133-267 Pa, preferably 133 Pa.
[0042] In a fifth aspect, the present invention further provides applications of the two-dimensional covalent organic framework material and the two-dimensional covalent organic framework metal composite material in water electrolysis catalysis, photocatalysis, drug delivery and gas separation.
[0043] The present invention has the following beneficial effects:
[0044] 1. The present invention can synthesize two covalent organic framework materials connected by imine and imidazole respectively from the same group of precursors only by adjusting the catalyst, and the preparation process of the method is simple.
[0045] 2. The two covalent organic framework materials with different pore sizes prepared by the present invention have high crystallinity, high specific surface area, good chemical stability and thermal stability, and achieve the purpose of effectively generating the desired topological structure in a selective manner.
[0046] 3. The present invention can also obtain a metal-complexed Pd / HT-COFs composite material through the special coordination environment of the ortho-imine in HT-COFs, which has good application in energy. BRIEF DESCRIPTION OF THE DRAWINGS
[0047] Figure 1 This is the synthesis route of the covalent organic framework HT-COFs material in Example 1.
[0048] Figure 2 This is the synthesis route of the covalent organic framework BI-HT-COFs material in Example 2.
[0049] Figure 3 N2 adsorption-desorption curve and pore size distribution diagram of the HT-COFs material prepared in Example 1.
[0050] Figure 4 N2 adsorption-desorption curve and pore size distribution diagram of the BI-HT-COFs material prepared in Example 2.
[0051] Figure 5 This is the XRD pattern of the HT-COFs material prepared in Example 1.
[0052] Figure 6 This is the XRD pattern of the BI-HT-COFs material prepared in Example 2.
[0053] Figure 7 This is the infrared spectrum of the HT-COFs material prepared in Example 1.
[0054] Figure 8 This is the infrared spectrum of the BI-HT-COFs material prepared in Example 2.
[0055] Fig. 9 This is a data chart of the chemical stability of the HT-COFs material prepared in Example 1.
[0056] Fig.10 This is a data chart of the chemical stability of the BI-HT-COFs material prepared in Example 2.
[0057] Fig.11 This is the thermogravimetric curve of the HT-COFs material prepared in Example 1.
[0058] Fig.12 This is the thermogravimetric curve of the BI-HT-COFs material prepared in Example 2.
[0059] Fig.13 This is the X-ray photoelectron spectrum of the Pd / H-COFs material in Example 3.
[0060] Fig.14 This is the transmission electron microscope EDS energy spectrum of the Pd / H-COFs material in Example 3. DETAILED DESCRIPTION
[0061] The present invention will be further described below in conjunction with specific embodiments, but the present invention is not limited to the following embodiments.
[0062] Unless otherwise specified, the experimental methods used in the following examples are conventional methods.
[0063] Unless otherwise specified, the reagents, materials, instruments, etc. used in the following examples can be obtained from commercial sources.
[0064] Example 1. Synthesis of HT-COFs
[0065] like Figure 1 As shown, the steps are as follows:
[0066] 15 mg HATP and 12 mg TPA were placed in a 10 mL polymerization tube, and then 0.5 mL of dioxane and 0.5 mL of mesitylene solvent were added, ultrasonically dispersed for 20 min, 0.1 mL of 1 M acetic acid aqueous solution was added, and ultrasonicated again for 2 min until mixed evenly, and freeze-pumped twice (77 K), and the tube was sealed. After it returned to room temperature, it was placed in a 150 ° C forced air oven and allowed to react for 14 days. After the reaction was completed, the heating was turned off, and the system returned to room temperature, and the precipitate was filtered and collected. It was washed thoroughly with tetrahydrofuran and dichloromethane, and the obtained product was placed in a vacuum drying oven at 100 ° C and dried overnight to obtain HT-COFs.
[0067] Test results:
[0068] 1. Figure 3 The N2 adsorption-desorption curve and pore size distribution of HT-COFs show that it has two pore sizes of ~1nm and ~1.3nm, with a specific surface area of 466m 2 / g, indicating that the obtained HT-COFs have a double-pore structure.
[0069] 2. Figure 5 This is the X-ray powder diffraction pattern of HT-COFs. 5.9° corresponds to the (100) crystal plane and 26° corresponds to the (001) crystal plane.
[0070] 3. Figure 7 The infrared spectrum of HT-COFs shows that the HT-COFs material of the present invention has a higher infrared spectrum at 3300-3500cm-1 compared with its monomer. -1 The amino signal at 1625 cm -1 The appearance of the imine peak after the reaction indicates that the reaction consumes the precursor and forms the imine bond.
[0071] 4. Chemical stability test method: Take 10 mg of newly prepared HT-COFs, put it into 1 mL of the corresponding solution, let it stand for 36 hours, filter it and wash it with tetrahydrofuran, and test the powder X-ray diffraction after vacuum drying at 100°C, and compare it with the sample without solvent treatment.
[0072] The results are as follows Fig. 9 As shown, HT-COFs have good chemical stability in conventional organic solvents, PBS aqueous solution and even 0.1 M HCl and 0.1 M KOH aqueous solution.
[0073] 5. Thermal stability: The results are as follows Fig.11 As shown, the decomposition temperature of HT-COFs material is higher than 450 °C, so it has good thermal stability.
[0074] Example 2. Synthesis of BI-HT-COFs
[0075] like Figure 2 As shown, the steps are as follows:
[0076] 15 mg HATP and 6 mg TPA were placed in a 10 mL polymerization tube, and then 0.5 mL of dioxane and 0.5 mL of mesitylene solvent were added, ultrasonically dispersed for 20 min, 0.1 mL of 1.4 M p-toluenesulfonic acid aqueous solution was added, and ultrasonicated again for 2 min until the mixture was uniformly mixed. After freezing-pumping cycles twice (77 K), the tube was sealed, and after it returned to room temperature, it was placed in a 150 ° C forced air oven and allowed to react for 14 days. After the reaction was completed, the heating was turned off, and the system returned to room temperature. The precipitate was collected by filtration and washed thoroughly with tetrahydrofuran and dichloromethane. The obtained product was placed in a vacuum drying oven at 100 ° C overnight to obtain BI-HT-COFs material.
[0077] Test results:
[0078] 1. Figure 4 The N2 adsorption-desorption curve and pore size distribution of BI-HT-COFs show that it has a uniform pore size of ~2.5 nm and a specific surface area of 532 m 2 / g, indicating that the structure of the obtained material is a single-pore structure.
[0079] 2. Figure 6 This is the X-ray powder diffraction pattern of BI-HT-COFs. 3.4° corresponds to the (100) crystal plane and 26° corresponds to the (001) crystal plane.
[0080] 3. Figure 8 The infrared spectrum of BI-HT-COFs shows that the BI-HT-COFs material of the present invention has a higher infrared spectrum at 3300-3500cm-1 compared with its monomer.-1 The amino signal at 1609 cm -1 The appearance of the imidazole C=N peak after the reaction indicates that the reaction consumed the precursor and the imidazole connection was formed.
[0081] 4. Chemical stability test method: Take 10 mg of the newly prepared BI-HT-COFs, put it into 1 mL of the corresponding solution, let it stand for 36 hours, filter it and wash it with tetrahydrofuran, and test the powder X-ray diffraction after vacuum drying at 100°C, and compare it with the sample without solvent treatment.
[0082] The results are as follows Fig.10 As shown, BI-HT-COFs have good stability in conventional organic solvents, PBS aqueous solution and even 0.1 M HCl and 0.1 M KOH aqueous solution.
[0083] 5. Thermal stability: The results are as follows Fig.12 As shown, the decomposition temperature of BI-HT-COFs material is higher than 500 °C, so it has excellent thermal stability.
[0084] Example 3. Synthesis of Pd / HT-COFs
[0085] Here are the steps:
[0086] 50 mg of palladium acetate was dissolved in 50 mL of dichloromethane, and then 25 mg of HT-COFs was added; the mixture was kept stirring at room temperature for 24 hours; the precipitate was collected by suction filtration, the product was washed with dichloromethane, and then dried under vacuum at 100° C. overnight to obtain Pd / HT-COFs powder.
[0087] Test results:
[0088] 1. If Fig.13 As shown, C, N, O, and Pd exist in the material, indicating that a Pd / HT-COFs composite material was obtained through the reaction.
[0089] 2. Fig.14 This is the transmission electron microscope EDS spectrum of Pd / H-COFs, with a scale of 100 nm. It can be seen from the figure that the four elements C, N, O, and Pd are evenly distributed in the Pd / HT-COFs material.
[0090] Summarize:
[0091] 1. Comparison of the materials obtained in Example 1 and Example 2 shows that the chemical compositions of the two two-dimensional covalent organic framework materials HT-COFs and BI-HT-COFs based on hexaaminotriphenyl group are not significantly different, but their crystallinity is significantly different, as shown in their X-ray powder diffraction patterns and infrared spectra. Figure 5-8As shown, it is proved that the covalent organic framework materials HT-COFs and BI-HT-COFs have porosity and regular ordered pore structure, so these two polymers have potential application value in water electrolysis catalysis, photocatalysis, drug delivery and gas separation.
[0092] 2. Covalent organic framework materials HT-COFs and BI-HT-COFs have porosity and regular ordered pore structure, but due to the obvious differences in the shape and size of the pores, the two frameworks can 12 Shows highly selective adsorption.
[0093] Although the present invention has been described in detail above with general descriptions and specific embodiments, it is obvious to those skilled in the art that some modifications or improvements may be made thereto based on the present invention. Therefore, these modifications or improvements made without departing from the spirit of the present invention all fall within the scope of protection claimed by the present invention.
Claims
1. A method for preparing a two-dimensional covalent organic framework material, comprising the following steps: S1, dissolving a monomer A containing an amino functional group and a monomer B containing an aldehyde functional group in a mixed solvent, adding a catalyst of acetic acid or p-toluenesulfonic acid, and ultrasonicating to obtain a mixed solution; S2. After the mixed solution is subjected to a vacuum-freezing-nitrogen circulation cycle, the tube is sealed for polymerization, and the system is allowed to stand until the system returns to room temperature, and then post-processed to obtain a two-dimensional covalent organic framework material HT-COFs or BI-HT-COFs.
2. The method for preparing a two-dimensional covalent organic framework material according to claim 1, characterized in that: In step S1, the monomer A is 2,3,6,7,10,11-hexaaminotriphenylhexahydrochloride; The monomer B is 1,4-benzenedicarboxaldehyde and / or 2,5-dimethoxybenzene-1,4-dicarboxaldehyde; The molar ratio of the monomer A to the monomer B is (0.3-1):1; The mixed solvent is composed of dioxane and mesitylene in a molar ratio of (0.1-1):1; The catalyst is added in the form of an aqueous solution; The concentration of the aqueous solution of acetic acid is 1-6M; The concentration of the aqueous solution of p-toluenesulfonic acid is 1-6M.
3. The method for preparing a two-dimensional covalent organic framework material according to claim 1 or 2, characterized in that: In step S1, the ultrasonic conditions are: time is 10-100 min, and ultrasonic frequency is 1-100 Hz; The catalyst is acetic acid, and in the corresponding mixed solution, the concentration of the monomer A is 10-20 mg / mL, and the concentration of the monomer B is 6-12 mg / mL; The catalyst is p-toluenesulfonic acid. In the corresponding mixed solution, the concentration of the monomer A is 10-20 mg / mL, and the concentration of the monomer B is 6-12 mg / mL.
4. The method for preparing a two-dimensional covalent organic framework material according to any one of claims 1 to 3, characterized in that: In step S2, the conditions of the vacuum-freezing-nitrogen circulation are: temperature of 75-80K, number of times of 1-6 times; The standing conditions are: temperature of 60-150° C., and time of 3-15 days.
5. The method for preparing a two-dimensional covalent organic framework material according to any one of claims 1 to 4, characterized in that: In step S2, the post-treatment includes: suction filtration, solvent washing, and vacuum drying; The solvent used in the solvent washing is at least one of methanol, dichloromethane, tetrahydrofuran and ethanol; The vacuum drying conditions are: temperature of 90-120° C. and vacuum degree of 133-267 Pa.
6. The two-dimensional covalent organic framework material obtained by the method according to any one of claims 1 to 5, characterized in that: The two-dimensional covalent organic framework material is an imine-connected two-dimensional covalent organic framework HT-COFs or an imidazole-connected two-dimensional covalent organic framework BI-HT-COFs; The structural formula of the HT-COFs is as follows: The structural formula of the BI-HT-COFs is as follows:
7. A two-dimensional covalent organic framework metal composite material, comprising the following components: the HT-COFs as described in claim 6 and Pd loaded on the HT-COFs.
8. The method for preparing the two-dimensional covalent organic framework metal composite material according to claim 7 comprises the following steps: adding the HT-COFs and a palladium source into a solvent, stirring, and post-treating to obtain the two-dimensional covalent organic framework metal composite material Pd / HT-COFs.
9. The preparation method according to claim 8, characterized in that: The palladium source is one or more of palladium acetate, palladium chloride and palladium pivalate; The solvent is one or more of dichloromethane, chloroform and acetonitrile; In the stirred system, the concentration of the HT-COFs is 0.1-5 mg / mL, and the concentration of the palladium source is 0.5-25 mg / mL; The stirring conditions are: temperature of 15-35° C. and time of 1-3 days.
10. Application of the two-dimensional covalent organic framework material according to claim 6 and the two-dimensional covalent organic framework metal composite material according to claim 7 in water electrolysis catalysis, photocatalysis, drug delivery and gas separation.